2018
DOI: 10.3390/molecules23051234
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Effectiveness of Magnetite Nanoparticles: Dependence upon Particle Size Probed by Experiment and Simulation

Abstract: The photothermal effect of nanoparticles has proven efficient for driving diverse physical and chemical processes; however, we know of no study addressing the dependence of efficacy on nanoparticle size. Herein, we report on the photothermal effect of three different sizes (5.5 nm, 10 nm and 15 nm in diameter) of magnetite nanoparticles (MNP) driving the decomposition of poly(propylene carbonate) (PPC). We find that the chemical effectiveness of the photothermal effect is positively correlated with particle vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…IONs have demonstrated to be effective PA in various applications. For instance, they can drive high barrier reactions, such as the clean decomposition of propylene carbonate [ 111 ]. Concerning biomedical applications, the intrinsic ability to generate heat within a short time under NIR laser irradiation makes IONs a novel promising hyperthermia agent.…”
Section: Iron Oxide Nanoparticles For Photothermal Therapymentioning
confidence: 99%
“…IONs have demonstrated to be effective PA in various applications. For instance, they can drive high barrier reactions, such as the clean decomposition of propylene carbonate [ 111 ]. Concerning biomedical applications, the intrinsic ability to generate heat within a short time under NIR laser irradiation makes IONs a novel promising hyperthermia agent.…”
Section: Iron Oxide Nanoparticles For Photothermal Therapymentioning
confidence: 99%
“…When Au is coupled with MMSN, the photothermal effect increased to a certain extent, which may be attributed to Au's surface electron oscillation after absorbing near-infrared light. As Fe 3 O 4 microspheres had stronger absorption in the near-infrared region than Au, and MNP had better photothermal conversion under nearinfrared light, 32,33 MNP temperature heating rate was higher than MMSN-Au under PT. However, things were different for magnetothermal properties because Au nanoparticles could not generate heat in an alternating electric field.…”
Section: Magnetothermal and Photothermal Propertiesmentioning
confidence: 99%
“…Johnson et al have proved by experiments and simulation that the heating ability is related to the volume of the nanoparticles, rather than the absorptivity of the particles. This dependence is associated to the fact that particles with larger heat capacities can heat larger volumes of their surrounding media for larger periods [25].…”
Section: Photothermal Properties Of Ionsmentioning
confidence: 99%
“…It was demonstrated that the greatest part of the heat generated by magnetite nanoparticles was effectively dissipated to the surroundings without producing significant undesirable changes of the particles such as crystalline phase transitions, agglomeration or fragmentation [24]. Recently, the photothermal effectiveness of IONs has been proved to depend on particle size: The effectiveness shows a good correlation with particle volume [25]. Several works using aggregated or individual IONs as PA in the first biological window have been described [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%